CLINICAL OUTCOMES OF NEOADJUVANT CONCURRENT CHEMORADIOTHERAPY USING VOLUMETRIC MODULATED ARC THERAPY IN PATIENTS WITH STAGE II-IVA MIDDLE AND LOWER THORACIC ESOPHAGEAL CANCER (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluation the initial efficacy and safety profile of neoadjuvant chemoradiotherapy utilizing volumetric modulated arc therapy in patients with middle-to-lower third, stage II-IVA esophageal cancer.Methods: This longitudinal descriptive study included 71 patients treated with preoperative chemoradiotherapy using the Paclitaxel-Carboplatin regimen and the volumetric modulated arc therapy technique.Results: The mean age of the patients was 56.1 years; 100% patients were male; stage III disease accounted for 53.5%; and the baseline lymph node metastasis (N+) rate was 70.4%. The overall response rate following neoadjuvant chemoradiotherapy was 90.1%; the resection rate after chemoradiotherapy was 91.5%; and the pathological complete response rate was 32.4%. Tumor stage and clinical response to chemoradiotherapy were significantly associated with the likelihood of achieving pathological complete response.Conclusion: Preoperative chemoradiotherapy using volumetric modulated arc therapy technique for middle-to-lower third squamous cell carcinoma of the esophagus is an effective and well-tolerated regimen with a high response rate.
Keywords: Esophageal cancer, pre-operative, VMAT, CROSS.